A technique modification in the cannulation to the innominate artery in the surgical treatment of aortic dissection. Issue 1 (December 2015) - Yu, Yang; Gu, Tianxiang; Shi, Enyi; Yu, Lei; Wang, Chun
Abstract Background A modified cannulation strategy to innominate artery was introduced which differs from traditional cannulation method used in aortic surgeries. Case presentation Four patients suffering from aortic dissections with or without other cardiac diseasees underwent surgical treatment by using the modified canulation technique. All patients had an uneventful perioperative period and discharged from the hospital without any complications. Conclusions Innominate artery cannulation using the modified cannula with "a hole in the back" is an easy and effective strategy for arch surgery.